Regional Value Added Through Local Production of Renewable Energy - Kosfeld, Reinhold; Gückelhorn, Franziska (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
Doubtlessly the ecological effects of renewable energies play an important role for the acceptance in the population, but local politicians need to introduce the economic benefits in the public debate as well. In particular a potential gain in regional value added through local production of renewable energy becomes the focus of attention for urban and rural communities. This study aims at quantifying these economic effects arising from the energy production through wind, sun, water and biogas for four German model regions: Trier, Hannover, Friesland and Nordschwarzwald. Especially the value added during the operating phase of a renewable energy production facility is of interest here. A procedure was developed accounting for direct and indirect effects on the value added. But also so called induced effects are considered generated through the partly spending of the additional incomes (direct and indirect). The main results show, that the average net value added differs widely between the various kinds of energy sources, but also within one energy source there are differences between the four model regions.